SYNTHESIS OF A Cd(II)-BASED 2D COORDINATION POLYMER WITH 1-HYDROXY-2-NAPHTHOIC ACID (Universal International Scientific Journal, 2026)
In this work, a new Cd(II) coordination polymer (HNA-CP) based on 4-hydroxy-1-naphthoic acid (HNA) was synthesized, and its structure was characterized by single-crystal X-raydiffraction. Crystallographic analysis showed that Cd(II) ions have separate coordination media and arecombined into an extended two-dimensional polymer frame.
Keywords: X-ray; 2D coordination polymer; 4-hydroxy-1-naphthoic acid (HNA)